Revisiting forever gained: income dynamics in the resettlement areas of Zimbabwe, 1983-1997. - Gunning, Jan Willem; Hoddinott, John F.; Kinsey, Bill; Owens, Trudy (Oxford University Press, 1999)
This paper examines income dynamics for a panel of households resettled on former white-owned farms in the aftermath of Zimbabwe's independence